Dedifferentiated chondrosarcoma with leukocytosis and elevation of serum G-CSF. A case report - Oda Yoshinao; Harimaya Katsumi; Matsuda Shuichi; Tanaka Kazuhiro; Yamamoto Hidetaka; Sakamoto Akio; Tsuneyoshi Masazumi; Iwamoto Yukihide (World Journal of Surgical Oncology, 2006)
Abstract Background G-CSF is known to function as a hematopoietic growth factor and it is known to be responsible for leukocytosis. G-CSF-producing tumors associated with leukocytosis include various types of malignancies. Case presentation We report the case of a 72-year-old man with dedifferentiated chondrosarcoma characterized by dedifferentiated components of malignant fibrous histiocytoma- or osteosarcoma-like features in addition to conventional chondrosarcoma, arising from his pelvic bone. After hemipelvectomy, when local recurrence and metastasis were identified, leukocytosis appeared and an elevated level of serum granulocyte-colony-stimulating factor (G-CSF) was also recognized. The patient died of multiple organ failure 2 months after surgery. Autopsy specimens showed that the histological specimens of the recurrence and metastasis were dedifferentiated components, without any conventional chondrosarcoma components. G-CSF was expressed only in the dedifferentiated components, not in the chondrosarcoma components, immunohistochemically. Conclusion This is the first report of chondrosarcoma, or any other primary bone tumor, with leukocytosis, probably stimulated by tumor-produced G-CSF from the dedifferentiated components.